Frequency of Prehospital Ambulance Utilization by Patients with Chronic Disease: A Retrospective Study - Sanjana, I Wayan Edi; Kamaryati, Ni Putu; Sagitha, I Gede Edy; Sari, Ni Made Candra Citra; Sutini, Ni Kadek (Babali Publisher, 2023)
Ambulance services are becoming a trend for early response to emergencies in major cities. The performance of the ambulance service will increase in line with the population and possible problems in the area. EMS services are essential at this time, as any life-threatening condition requires immediate action to prevent disability and death. Ambulances are required to provide assurance to chronically ill patients that the service they provide is adequate and can handle them in case of deterioration. This study aims to describe the frequency of pre-hospital ambulance use in patients with chronic diseases. This research method is an observational study with a retrospective approach to find the frequency of ambulance use by chronic diseases during the period 2019-2021. The results showed the three highest cases of pre-hospital ambulance use in Denpasar City were accident, fire and evacuation services for sick patients. The use of prehospital ambulances by chronic diseases has not reached half of the ambulance services. Stroke, diabetes mellitus and heart disease are the three most common chronic diseases that use pre-hospital ambulance services.